(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The research aims at potential activities of leaf methanolic extracts of Leptadenia hastata against clinical Escherichia coli and extraction, phytochemicals and biochemical tests to the plant and organism. Escherichia coli is Gram negative, non-capsulated, bacillus, clinically important bacteria mostly isolated clinically and capable to cause gastro enteritis, urinary tract infections, diarrhea among others. L. hastata is a climbing shrub that produces flexible latex which become woody at the base. Potential activities of L. hastata leaf methanolic extracts against clinical Escherichia coli were observed. L. hastata leaf were sampled, Phyto-chemically screened using methanol and processed using Di-MethylSulfurOxide (DMSO). Clinical Bacterial Isolates were collected from Murtala Muhammed Specialist Hospital Kano, Kano State, Nigeria, investigated and screened for E. coli using Gram’s staining technique and some biochemical tests procedure for confirmation. L. hastata leaf methanolic extracts were processed against the isolates. Four (4) E. coli were found and tested against leaf methanolic extracts of L. hastata at different concentrations of 125, 250, 500 and 1000 mg/mL respectively. Activity was observed directly proportional to the concentrations, where the Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) were at 500 and 1000 mg/mL accordingly. The research may lead to effective drug development against the clinical E. coli to address its pathogenicity, for the Public Health benefit. It is recommended that further research should be carried out to determine bioactive components of L. hastata leaf, toxicity level tests and Molecular characterization to the isolate (E. coli).